Inhaled Nitric Oxide for the Prevention of Impaired Arterial Oxygenation during Myocardial Revascularization with Extracorporeal Circulation - I. A. Kozlov; A. A. Romanov; E. V. Dzybinskaya; A. E. Balandyuk (Общая реаниматология, 2011)
Objective: to study the efficacy of inhaled nitric oxide used intraoperatively to prevent lung oxygenating dysfunction in patients with coronary heart disease after myocardial revascularization under extracorporeal circulation (EC). Subjects and methods. Thirty-two patients aged 55.0±2.0 years were examined. The inclusion criteria were the standard course of surgical intervention (the absence of hemorrhage, acute cardiovascular insufficiency, perioperative myocardial infarction, etc.), a pulmonary artery wedge pressure of less than 15 – mm Hg throughout the study, and the baseline arterial partial oxygen tension/inspired mixture oxygen fraction (PaO2/FiO2) ratio of at least 350 mm Hg. There was a control group (n=21; Group 1) that used no special measures to prevent and/or to correct lung oxygenating dysfunction and Group 2 (n=11) that received inhaled nitric oxide. Ihe administration of inhaled nitric oxide at a concentration of 10 ppm was initiated after water anesthesia, stopped during EC, and resumed in the postperfusion period. Results. At the end, PaO2/FiO2 and intrapulmonary shunt fraction did not differ between the groups (p>0.05). Before EC, the patients receiving inhaled nitric oxide had a lower intrapulmonary blood shunting (8.9±0.7 and 11.7±1.0%; p<0.05). There were no intergroup differences in the values of PaO2/FiO2 at this stage. In the earliest postperfusion period, PaO2/FiO2 was higher in Group 2 than that in Group 1. At the end of operations, Groups 1 and 2 had a PaO2/FiO2 of 336.0±16.8 and 409.0±24.3 mm Hg, respectively (p<0.05) and an intrapulmonary shunt fraction of 14.5±1.0 and 10.4±1.0% (p<0.05). At the end of surgery, the rate of a reduction in PaO2/FiO2 to the level below 350 mm Hg was 52.4±11.1% in Group 1 and 18.2±11.6% in Group 2 (p<0.05). Six hours after surgery, PaO2/FiO2 values less than 300 mm Hg were diagnosed in 61.9±10.5% of Group 1 patients and in 27.3±13.4% of Group 2 ones (p<0.05). Conclusion. The prescription of inhaled nitric oxide at a concentration of 10 ppm to patients with the baseline normal level of PaO2/FiO2 ensured the prevention of lung oxygenating dysfunction in the postperfusion and early postoperative period. The preventive effect of inhaled nitric oxide was steady-state: 6 hours following myocardial revascularization under EC, the patients intraoperatively receiving inhaled nitric oxide showed a 2.3-fold lower rate of lung oxygenating dysfunction (PaO2/FiO2 less than 300 mm Hg) than the controls. Key words: lung oxygenating function, inhaled nitric oxide, operations under extracorporeal circulation, lung ischemia-reperfusion.